MODA, CHWYT REKLAMOWY CZY KONIECZNOŚĆ? – ROZWAŻANIA O ISTOCIE DZIAŁAŃ INNOWACYJNYCH W EDUKACJI - Zawadzka-Bartnik, Elżbieta (Neofilolog, 2018)
The purpose of this paper is to indicate an ambiguous understanding of the notion of innovation in education and misunderstandings connected with it. It also involves a critical analysis of the main sources of difficulty in choosing and executing pedagogical innovations, as well as encourages reflection on and mobilisation for self-preparedness to make changes in the profession. This paper will discuss arguments confirming the necessity of innovative actions in education. Examples of actual innovative actions and ostensible actions/pseudo-innovations will be given, characteristics of innovators and “Pharisees of innovation” will be presented. This paper will also demonstrate the possibilities of organising pedagogical innovations efficiently, and the possible support for innovative teachers, leading to the increase in the efficiency of their actions.